Pengaruh Kepemimpinan Demokratis dan Work-life Balance Terhadap Kinerja Karyawan Perusahaan Tekstil PT. Duta Interlining Indonesia - Simarmata, Elizabeth Anabella Martina Bintari (Global Research on Economy, Business, Communication, and Information, 2023)
Employees' performance is the key factor of company development.   Democratic leadership and work-life balance are crucial factors in employee performance. This general view is widely accepted. However, the logic in it is context specific. In other words, a specific context can perform a specific behavior. This study concerns PT. Duta Interlining Indonesia. As a workforce-oriented company, the influence of leadership and work-life balance on performance should be very large. This study is intended to confirm this notion. Therefore, the authors collect data from 100 employees as the sample. Using multiple linear regression analysis, data analysis with IBM  SPSS 26 reveals that democratic leadership and work-life balance positively influence employee performance. The two independent variables explain employees' performance by 25%, as much as 75% caused by other factors. The other factors can be uncovered by further research.